Analysis of Physical and Mechanical Properties of Multiwalled Carbon Nano Tubes (MW-CNTs) Reinforced Mineral Composites as an Environmentally Friendly Machine Structure - Setiyawan, Khanif; Sugiantoro, Bambang; Sutisna, Utis; Rusnaldhy, Rusnaldhy; Widyanto, Susilo Adi (Jurnal Rekayasa Mesin, 2019)
The Rigidity, absorption resistance, and vibration damping are important factors for the formation of static components and structures with excitation force loads. The development of new materials from composites for metal substitution has achieved better properties. The use of rocks with reinforcement CNTs can produce higher damping properties than metal casting, but young modulus is low. The Composite polymer material made from volcanic rock can be cast with epoxy with a variation of the aggregate ratio using compressive press able to improve mechanical properties. The volcanic rocks used in this study are granite, silica, and volcanic sand, using carbon nanotubes MW-CNTs as reinforcement. This research was conducted to produce structures with high strength and rigidity. The material are classified dimensions coarse (0,2-0,5 mm), medium (20 Î¼m-50 Î¼m), and fine (0.125mm/0.50 mm). Based on SEM/EDX test results of granite, silica, and volcanic sand have high silica content (with the sharp crystalline form that has the potential to strengthen the composite bond. The fly ash has high silica content, with round and fine crystals form. The specimen formation method refers to the dimensions of the composite specimen bending test according to ASTM D 645. The combination of materials that warns hardness and elongations, in separate tests of volcanic sand and granite which has the highest hardness, the use of CNTs can increase the hardness of 15% in each specimen, increase bending testing at 220% to 300%, prove that the inside of the crystalline bond forms ductile properties.